PENGARUH KUALITAS PELAYANAN DAN CITRA LEMBAGA TERHADAP KEPUTUSAN PENGGUNAAN JASA PENDIDIKAN SERTA DAMPAKNYA PADA KEPUASAN MAHASISWA ( penelitian pada mahasiswa STIE Muhammadiyah Bandung semester VII, V, III, program studi Akuntansi dan Manajemen ) - Fitriani, Iis Dewi; Mubarok, Rifqi Ali (2018)
This research was conducted at the STIE Muhammadiyah Bandung on courses Accounting and Management. It used 4 variables; the independent variables which consist of Service Quality, Image of Institution intermediate variables are making the decision to use the services and the dependent variable is the student satisfaction. The data is collected by using a closed questionnaire which is consisting of an introduction and the contents of the questionnaire. It is divided into two parts: 1. The respondent data which consists of age, sex, year of entry. 2. Assessment of the marketing mix variables, making the selection, student satisfaction. The measurement scale used is Likert scale which consists : 1 represents strongly disagree, 2 represents disagree, 3 represents less agree, 4 represents agree and 5 represents strongly agree. The number of samples involved in this study were 232 respondents which is drawn from 554 people (total population). Validity test conducted on 26 respondents as a test of the questionnaire. Reliability test, measuring devices used in this research is to examine the correlation between items (inter - item correlation) by calculating the value of Cronbach Alpha. The method used in this research is descriptive analysis and verificative analysis. The technique of data analysis used is correlation analysis to determine the degree of closeness of the relationship between the study variables and path analysis techniques to determine the influence (directly or indirectly) of the independent variable on the dependent variable. In operation, the data analysis is using SPSS 21,00 software. The result of data processing is obtained as follows: There is the influence of the service quality and image institution through decision to use the services simultaneously by 50% and the remaining 41% is contributed by other variables which are not examined in this study.. There is the effect of the decision to use the services of student satisfaction at 64,1% and the remaining 35,9% is contributed by other variables which is not examined in this study.